Indonesian Climbing Federation Management in Lubuk Linggau City, Sumatera Selatan - Trinanda, Aditya; Sulaiman, Sulaiman; Mukarromah, Siti Baitul (Journal of Physical Education and Sports, 2021)
The background of this research is that sport climbing as a sport has the potential to contribute to the future development of sports in Indonesia. Lubuk Linggau City is home to various sports that have a chance to earn a gold medal in 2013, including sport climbing. Since 2014, the sport climbing has seen a fall in achievement at city, provincial, and national levels. The goal of this study is to examine management of the following functions: Planning, Organizing, Actuating, and Controlling. This study employs a qualitative approach. Observation, interviews, and documentation are used to collect data. Administrators, coaches, athletes, and parents provided data. The data analysis process involved data triangulation in three stages: 1) data reduction, 2) data display, and 3) conclusion drafting. The study's findings include the following: 1) Management planning (FPTI) meets the categorization criteria, namely it is clear who, what, when, where, and how to do it; 2) Organizing, management (FPTI) meets the categorization criteria, namely comprehensive management, work mechanism, no written job description, and routine activities that are discussed at the start of the year; 3) Actuating, management (FPTI) meets the categorization criteria, namely it is complete management, work mechanism, and there are routine activities that The study's conclusions show that: (1) Planning: the Indonesian sport climbing federation's management is excellent; (2) Organizing: the Indonesian sport climbing federation's management is pretty good; and (3) Actuating: the Indonesian sport climbing federation's management is fairly good. (4) Controlling: the Indonesian sport climbing association is quite well run.